Alliances and corporate governance - Bodnaruk, Andriy; Massa, Massimo; Simonov, Andrei (Journal of Financial Economics, 2013)
We study the link between a firm's quality of governance and its alliance activity. We consider alliances as a commitment technology that helps a company’ Chief Executive Officer overcome agency problems that relate to the inability to ex ante motivate division managers. We show that well-governed firms are more likely to avail themselves of this technology to anticipate ex post commitment problems and resolve them. The role of governance is particularly important when the commitment problems are more acute, such as for significantly risky/long-horizon projects (“longshots”) or firms more prone to inefficient internal redistribution of resources (conglomerates), as well as in the absence of alternative disciplining devices (e.g., low product market competition). Governance also mitigates agency issues between alliance partners; dominant alliance partners agree to a more equal split of power with junior partners that are better governed. An “experiment” that induces cross-sectional variation in the cost of the alliance commitment technology provides evidence of a causal link between governance and alliances.